2020
DOI: 10.1002/mp.14095
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive scan duration in SPECT: Evaluation for radioembolization

Abstract: Purpose: It may be challenging to select the optimal scan duration for single-photon emission computed tomography (SPECT) protocols because the activity distribution characteristics can differ in every scan. Using simulations and experiments, we investigated whether the scan duration can be optimized for every scan separately by evaluating the activity distribution during scanning. We refer to this as adaptive scanning. Methods: The feasibility of adaptive scanning was evaluated for the detection of extrahepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…van der Velden et al (2019a) demonstrated that activity recoveries and the lung-shunting can be accurately retrieved when using faster acquisitions (using a one minute instead of 20 min scan duration; 20× more noise). Dietze et al (2020a) demonstrated that extrahepatic depositions could be accurately retrieved when using faster acquisitions (using a mean acquisition duration of five minutes instead of 20 min; 4× more noise). And Kunnen et al (2020) demonstrated that the use of lower activity levels can provide quantitative accurate results (imaging 100 MBq instead of 2 GBq 90 Y; 20× more noise).…”
Section: Discussionmentioning
confidence: 99%
“…van der Velden et al (2019a) demonstrated that activity recoveries and the lung-shunting can be accurately retrieved when using faster acquisitions (using a one minute instead of 20 min scan duration; 20× more noise). Dietze et al (2020a) demonstrated that extrahepatic depositions could be accurately retrieved when using faster acquisitions (using a mean acquisition duration of five minutes instead of 20 min; 4× more noise). And Kunnen et al (2020) demonstrated that the use of lower activity levels can provide quantitative accurate results (imaging 100 MBq instead of 2 GBq 90 Y; 20× more noise).…”
Section: Discussionmentioning
confidence: 99%
“…However, some assumptions can be made based on current clinical care. For instance in radioembolization (which is of one the proposed applications for interventional SPECT scanning), it has been demonstrated that various quantitative measures (e.g., lung‐shunting fraction, tumor uptake ratio) can be accurately determined down to 1/10th of the clinically used number of counts 14‐16 . These findings suggest that the flat panel detector (which similarly has a lower count rate) should also be able to retrieve accurate clinical results.…”
Section: Discussionmentioning
confidence: 99%